2015
DOI: 10.1016/j.bbadis.2015.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Fructose consumption reduces hippocampal synaptic plasticity underlying cognitive performance

Abstract: Metabolic syndrome (MetS) is a global epidemic, which involves a spectrum of metabolic disorders comprising diabetes and obesity. The impact of MetS on the brain is becoming to be a concern, however, the poor understanding of mechanisms involved has limited the development of therapeutic strategies. We induced a MetS-like condition by exposing mice to fructose feeding for 7 weeks. There was a dramatic deterioration in the capacity of the hippocampus to sustain synaptic plasticity in the forms of long-term pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 79 publications
3
44
0
Order By: Relevance
“…Dietary fructose has emerged as a major contributor to the current epidemic of metabolic disorders [37], based on its effects on hepatic de novo lipogenesis, abdominal obesity, cholesterol and insulin resistance [8]. More recently, fructose was found to compromise synaptic plasticity, adult neurogenesis [9], and the capacity of neural circuits to cope with the effects of brain injury [10]. Fructose appears to induce a stage of metabolic dysfunction in the brain, negatively impacting cognitive function [10].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary fructose has emerged as a major contributor to the current epidemic of metabolic disorders [37], based on its effects on hepatic de novo lipogenesis, abdominal obesity, cholesterol and insulin resistance [8]. More recently, fructose was found to compromise synaptic plasticity, adult neurogenesis [9], and the capacity of neural circuits to cope with the effects of brain injury [10]. Fructose appears to induce a stage of metabolic dysfunction in the brain, negatively impacting cognitive function [10].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a high sucrose diet not only promotes obesity, but also may interfere with the anti-inflammatory effects of high n-3 FAs in adipose tissue [22]. This is relevant to patients being treated for breast cancer because our data suggest that this population consumes up to 32% of kilocalories from added sugars (T. Orchard, unpublished data), an amount that equals or exceeds levels found to be harmful in animal models examining neuroinflammation, neurogenesis, and cognition [2730]. …”
Section: Effects Of Chemotherapy In the Brainmentioning
confidence: 92%
“…2 and 3) (Agrawal and Gomez-Pinilla, 2012). Our research has revealed the harmful impact of fructose on the brain (Agrawal and Gomez-Pinilla, 2012; Cisternas et al, 2015; Gomez-Pinilla, 2008) such that the animals on fructose show impaired memory and learning skills, as well as reductions in proteins re lated to brain plasticity and mitochondrial bioenergetics (Figs. 1–3) (Agrawal and Gomez-Pinilla, 2012).…”
Section: The Threat Of the New Epidemic Of Metabolic Disordersmentioning
confidence: 99%
“…In addition, the capacity of the hippocampus to sustain synaptic plasticity in the forms of long-term potentiation (LTP) and long-term depression (LTD) was seriously compromised (Cisternas et al, 2015). Fructose exposure also reduced the number of contact zones and the size of postsynaptic densities (PSDs) in the hippocampus, which changes were concomitant to a decrease in hippocampal neurogenesis (Cisternas et al, 2015). The results of these studies challenge the current view that the effects of diet-induced metabolic abnormalities are restricted to the periphery.…”
Section: The Threat Of the New Epidemic Of Metabolic Disordersmentioning
confidence: 99%
See 1 more Smart Citation